Trends in the Use of Short-Term Mechanical Circulatory Support in the United States – An Analysis of the 2012 – 2015 National Inpatient Sample. Issue 6 (2nd November 2019) - Panhwar, Muhammad Siyab; Gupta, Tanush; Karim, Adham; Khera, Sahil; Puri, Rishi; Nallamothu, Brahmajee K.; Menon, Venu; Khot, Umesh N.; Bhatt, Deepak L.; Kapadia, Samir R.; Naidu, Srihari S.; Kalra, Ankur
ABSTRACT: Background : We aimed to study the use patterns of short-term mechanical circulatory support (MCS) for cardiogenic shock and associated in-hospital outcomes. Methods : We queried the National Inpatient Sample from 2012 to 2015 to identify patients with a diagnosis of CS, stratified by presence of acute myocardial infarction (AMI-CS or non-AMI-CS). We then studied trends in the use of short-term MCS. Our primary outcome was in-hospital mortality. Results : Of 422, 575 patients, 44.7% had AMI-CS. From 2012 to 2015, we observed a decrease in use of overall MCS (23.9% to 20.5%, Ptrend < 0.001). The use of intra-aortic balloon pump (21.8% to 16.8%, Ptrend < 0.001) declined, whereas that of percutaneous ventricular assist devices (1.9% to 2.9%, Ptrend < 0.001) and extracorporeal membrane oxygenation/percutaneous cardiopulmonary support (ECMO/PCPS; 1.3% to 2.0%; Ptrend = 0.01) increased. In-hospital mortality of CS remained similar in the overall cohort (38.2% to 38.2%, Ptrend = 0.39) and in the non-AMI-CS (38.8% to 38.3%, Ptrend = 0.53) and AMI-CS cohort (37.6% to 38.1%, Ptrend = 0.46) subgroups. Conclusion : We observed a decrease in the use of IABP for CS, while the use of pVAD and ECMO/PCPS increased. However, in-hospital mortality remained similar over time in both AMI-CS and non-AMI-CS patients.